The usefulness of the adenosine deaminase assay for diagnosing tuberculosis pleuritis in immunocompromised patients at Dr George Mukhari tertiary laboratory, Pretoria - Molaudzi, Mulalo (University of Limpopo (Medunsa Campus), 2012)
Mycobacterium tuberculosis is the most common cause of death world-wide and its incidence has been steadily increasing, which is more evident when comparing the global tuberculosis (T8) incidence of 9.24 million in 2006 to 9.27 million cases in 2007. African countries are the second most affected by the epidemic and South Africa is among the 22 highest burden countries most affected by T8 with a very high number of cases relative to the total population. The early diagnosis of tuberculosis and screening of contacts is the cornerstone for controlling spread of active T8 infection. T8 diagnosis becomes even more challenging in patients with immunosuppression (for example in human immunodeficiency virus (HIV) infected), in the case of latent infection and extra pulmonary T8 such as pleural T8. The definitive diagnosis of pleural T8 depends on the demonstration of M. tuberculosis in sputum, pleural fluid and pleural biopsy. Although acid fast bacilli (AF8) microscopy is a rapid, inexpensive and relatively simple method, it has low sensitivity. The culture method is more sensitive than AF8 microscopy, detecting 25-37% of all pleural tuberculosis cases however it takes 4 to 8 weeks for a visible growth on a solid medium. Therefore it is important to find a rapid and reliable test for the diagnosis of pleural T8 particularly in developing countries such as South Africa where there is a high T8 incidence and HIV infection rate.
Thesis (MSc (Med)(Microbiology)) -- University of Limpopo, 2012.
Keywords: Adenosine; Adenosine deaminase